Systematic synthesis of a 6-component organic-salt alloy of naftopidil, and pentanary, quaternary and ternary multicomponent crystals - Dandela, Rambabu; Tothadi, Srinu; Marelli, Udaya Kiran; Nangia, Ashwini (IUCrJ, 2018)
The single-crystal X-ray structure of a 6-component organic-salt alloy (hexanary) of naftopidil (1) (an active pharmaceutical ingredient) with benzoic acid (2) and four different hydroxy-substituted benzoic acids, i.e. salicylic acid (3), 2,3-dihydroxybenzoic acid (4), 2,4-dihydroxybenzoic acid (5) and 2,6-dihydroxybenzoic acid (6), is reported. The hexanary assembly originates from the observation that the binary salts of naftopidil with the above acids are isostructural. In addition to the 6-component solid, we also describe five 5-component, ten 4-component, and ten 3-component organic-salt alloys of naftopidil (1) with carboxylic acids (2)-(6). These alloys were obtained from different combinations of the acids with the drug. The synthetic design of the multicomponent organic alloys is based on the rationale of geometrical factors (shape and size) and chemical interactions (hydrogen bonds). The common supramolecular synthon in all these crystal structures was the cyclic N+ - H center dot center dot center dot O- and O-H center dot center dot center dot O hydrogen-bonded motif of R-2(2) (9) graph set between the 2-hydroxyammonium group of naftopidil and the carboxylate anion. This ionic synthon is strong and robust, directing the isostructural assembly of naftopidil with up to five different carboxylic acids in the crystal structure together with the lower-level multicomponent adducts. Solution crystallization by slow evaporation provided the multicomponent organic salts and alloys which were characterized by a combination of single-crystal X-ray diffraction, powder X-ray diffraction, NMR and differential scanning calorimetry techniques.